STUDI MENGENAI PERAN KUALITAS LAYANAN DALAM MEMBENTUK KEPUASAN DAN SIKAP PELANGGAN TERHADAP MEREK, SERTA KONSEKUENSINYA PADA MINAT MEREFERENSIKAN MEREK (Studi pada Salon Lie Kuang® di Kota Semarang) - Maharani, Dea Irnita (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2012)
The purpose of this study is to explore theoretical model on research gap about of service quality on referencing intention to brand by adding intervening variable, brand attitude, through the influence of customer satisfaction.The object of research in this study is the Lie Kuang Hair and Beauty Salon Semarang. The problem of this research is coming from the business phenomenon that figures the declining of new customers from the year 2010-2011. This problem indicates that the company still have to evaluates the effectiveness of its strategies in deliverying the best service quality.This study uses Structural Equation Modelling (SEM) analysis, ran by AMOS program Ver.18 as an analytical tool for the 150 respondents in accordance with the rules of minimum sample size to 5 or more constructs. Proposed research model can be accepted with the assumption that value of Standardized Residual Covariance nothing more than ± 2.58 and the determinant of sample covariance matrix = 1,124. The measurement of exogenous and endogenous constructs tested using confirmatory analysis. Moreover, the Goodness-of-Fit test of full model was analyzed using the SEM in which the value Chi-square = 96,151; probability = 0,192; GFI = 0,923; AGFI = 0.891; Cmin / DF = 1,131; TLI = 0.989; CFI = 0.991; and RMSEA = 0.030; is in the range of values expected. The findings of this study give conclusions proving that good core service quality and peripheral service quality can improve the level of customer satisfaction. Moreover, the great customer satisfaction has positively created the positive brand attitude, and finally, the attitude has its positive effect to referencing intention toward the brand.